Poured Out: A Kenotic Approach to Initiating Children at a Distance from the Church. (September 2019) - Johnson, Sarah Kathleen
A kenotic theology of infant initiation that emphasizes extending the self-giving of God through the sacraments is an alternative to a covenantal approach when celebrating Christian initiation in an American religious landscape characterized by declining participation in religious institutions, a growing population who identify as nonreligious, and increasing uncertainty about matters of faith. This study is anchored in twenty-one stories emerging from qualitative interviews with Protestant clergy about their experience of receiving requests for infant initiation. Analysis of interview data reveals five types of distance from the church (formal, relational, historic, theological, and moral), four primary motivations prompting families at a distance to request infant initiation (family celebration, cultural tradition, concern for salvation, and spiritual connection), and five approaches clergy take in responding to requests (safeguarding, hospitality, compassion, conviction, and evangelical opportunity). Engaging Chauvet, Belcher, Peirce, and Hughes, a kenotic approach invites the church to pour itself out, without expectation of reward, and with the risk of loss, as an extension of the self-giving of God. A kenotic approach invites participants with a range of relationships with the church to bring their own motivations and meanings which, through encounter and dialogue, may enrich the practice for all involved, including clergy and congregations, as a fusion of meaning is produced collaboratively.